2023
DOI: 10.3390/jmse12010057
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Sand-Scouring Characteristics of Pulsed Submerged Jets Based on Experiments and Numerical Methods

Hongliang Wang,
Xuanwen Jia,
Chuan Wang
et al.

Abstract: Water-jet-scouring technology finds extensive applications in various fields, including marine engineering. In this study, the pulse characteristics are introduced on the basis of jet-scouring research, and the sand-scouring characteristics of a pulsed jet under different Reynolds numbers and the impact distances are deeply investigated using Flow-3D v11.2. The primary emphasis is on the comprehensive analysis of the unsteady flow structure within the scouring process, the impulse characteristics, and the geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Positioned at the forefront of technological advancements, cavitation bubble technology finds primary applications in sectors including ships, chemical industries, medicine, and other fields. The water jet-induced cavitation bubble, recognized for its extensive impact range, high efficiency, and eco-friendliness, is extensively utilized in ship maintenance and chemical equipment cleaning [1][2][3][4][5][6]. In medicine, ultrasound-induced cavitation bubbles are used in cancer treatment, stone crushing, and gingival surgery owing to their small impact area and large impact force [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Positioned at the forefront of technological advancements, cavitation bubble technology finds primary applications in sectors including ships, chemical industries, medicine, and other fields. The water jet-induced cavitation bubble, recognized for its extensive impact range, high efficiency, and eco-friendliness, is extensively utilized in ship maintenance and chemical equipment cleaning [1][2][3][4][5][6]. In medicine, ultrasound-induced cavitation bubbles are used in cancer treatment, stone crushing, and gingival surgery owing to their small impact area and large impact force [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, this technology still has drawbacks, including large dimple sizes and high energy dissipation [7]. The application of cavitation water jet peening (CWJP) involves generating cavitation bubbles through the shearing effect of a high-speed water jet in an artificially submerged environment, leading to material removal [8][9][10]. Research conducted by Han et al [11] suggested that due to the inclination error in vertical jetting, uneven removal depths were observed in the pits generated during the immersion-based pulsed cavitation jet peening process.…”
Section: Introductionmentioning
confidence: 99%